The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ene.15178
|View full text |Cite
|
Sign up to set email alerts
|

Chiasmatic lesions on conventional magnetic resonance imaging during the first event of optic neuritis in patients with neuromyelitis optica spectrum disorder and myelin oligodendrocyte glycoprotein‐associated disease in a Latin American cohort

Abstract: Background and purpose Optic neuritis (ON) is often the initial symptom of neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein‐associated disease (MOGAD). We aimed to compare the frequency and pattern of chiasmatic lesions in MOGAD‐related ON (MOGAD‐ON) and NMOSD‐related ON (NMOSD‐ON) using conventional brain imaging (magnetic resonance imaging [MRI]) in Latin America (LATAM). Methods We reviewed the medical records and brain MRI (≤30 days from ON onset) of patients with a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, suggestive lesions in patients who present ON, myelitis, or cerebral/cortical syndromes may help to distinguish both conditions, especially when these symptoms cannot be differenced at presentation. 23,28,36…”
Section: Discussionmentioning
confidence: 99%
“…However, suggestive lesions in patients who present ON, myelitis, or cerebral/cortical syndromes may help to distinguish both conditions, especially when these symptoms cannot be differenced at presentation. 23,28,36…”
Section: Discussionmentioning
confidence: 99%
“…Spinal lesions were similarly rare in MOGAD (0%) as MS (4.4%) and AQP4‐ab‐positive NMOSD (0%) 118 . The appearance of asymptomatic lesions was not related to a higher risk of subsequent relapse at follow‐up, but further studies are needed 105 . Shah et al.…”
Section: Role Of Mri At Follow‐upmentioning
confidence: 99%
“…118 The appearance of asymptomatic lesions was not related to a higher risk of subsequent relapse at follow-up, but further studies are needed. 105 Shah et al found that asymptomatic optic nerve enhancement occurred in 16.8% of AQP4-ab-positive NMOSD patients with preceding ON and new asymptomatic enhancement was observed only in 1.8% of patients. 119 A subanalysis from the inebilizumab study (N-MOmentum randomized placebo-controlled trial) in NMOSD patients found that 51%, 3%, and 18% of MRI showed asymptomatic optic nerve, brain, and spinal cord gadolinium-T1 MRI enhancement during an interattack surveillance MRI (in the absence of adjudicated attacks), respectively.…”
Section: Role Of Mri At Follow-upmentioning
confidence: 99%
See 2 more Smart Citations